Correlation, Regression and Path analysis among yield and yield traits in Triticum dicoccum - Saleh, Maysoun M.; Moussa, Dyab S.; Alkaraki, Nader I.; Abdurahman, Abbas Lateef (Journal of Experimental Sciences)
Seven wheat genotypes (Triticum dicoccum) and the local check sham5 were planted all at Al-Ghab and Izra Research centers in The General Commission for Scientific Agricultural Research in Syria during growing season 2010/2011. Yield components (number of total and fertile tillers per plant, number and weight of grains per spike, weight of thousand grain and individual plant grain yield) were studied in two sites in order to predict their effect and to determine their effects on grain yield in order to define selection criteria for grain yield. Results revealed all studied traits except total tillers number were positively correlated with grain yield, and only (fertile tillers number and grain number per spike and grain weight per spike) had a significant regression with grain yield and these traits can explain about (27.6, 67.7, 62.2)% respectively of the variation final grain yield. Results of path analysis indicated that the direct effect of fertile tillers per plant and grain weight per spike on grain yield was positive and high (0.6178, 0.7563) respectively, so that we can depend on them in breeding program as selection criteria to increase grain yield in plant.